The Impact of Green Accounting Implementation, Corporate Social Responsibility (CSR), and Green Innovation on the Value of Companies in the Energy Sector - Wardoyo, Muhammad Jagad Samodera; Achyani, Fatchan (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the influence of green accounting, green innovation and corporate social responsibility on corporate value. This research is a quantitative study with an empirical approach conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sampling technique used in this study was purposive sampling based on certain predetermined criteria, resulting in 51 analysis units. The data used are secondary data obtained from annual reports and company sustainability reports. The data analysis method used is multiple linear regression analysis to test the effect of each independent variable on corporate value, proxied by Tobin 's q. The results show that green accounting, green innovation and corporate social Corporate responsibility has a significant influence on corporate value. social Responsibility has a positive influence, indicating that transparency of social activities through good disclosure standards can strengthen a company's legitimacy and provide a positive signal to investors, increasing the company's market value. Meanwhile, green accounting and green Innovation has a significant, negative, influence on firm value. This indicates that investors in the energy sector still view environmental costs and investments in green innovation as operational burdens and financial risks that can reduce a company's net profit in the short term. These findings are expected to contribute to the development of the literature and provide consideration for company management and investors in understanding the strategic factors that influence firm value in the energy sector.